To simplify the expression \((6^{-3})^7 \times \frac{6^{20}}{6^{-2}}\), we will use the properties of integer exponents.
-
Simplifying \((6^{-3})^7\): Using the power of a power property, \((a^m)^n = a^{m \cdot n}\): \[ (6^{-3})^7 = 6^{-3 \cdot 7} = 6^{-21} \]
-
Simplifying \(\frac{6^{20}}{6^{-2}}\): Using the quotient property, \(\frac{a^m}{a^n} = a^{m-n}\): \[ \frac{6^{20}}{6^{-2}} = 6^{20 - (-2)} = 6^{20 + 2} = 6^{22} \]
-
Now combine the two parts: We now have: \[ 6^{-21} \times 6^{22} \] Again using the product property, \(a^m \times a^n = a^{m+n}\): \[ 6^{-21 + 22} = 6^{1} = 6 \]
So, the expression simplifies to:
\[ 6 \]
Since the problem prompts for an improper fraction form, we can express 6 as:
\[ \frac{6}{1} \]
Therefore, the final simplified expression is:
\[ \frac{6}{1} \]